Solidarity: Its Levels of Operation, Relationship to Justice, and Social Causes (Diametros, 2015)
The paper provides an analysis of the relationship between the concepts of justice and solidarity. The point of departure of the analysis is Ruud ter Meulen’s claim that these concepts are different but mutually complementary, i.e. are two sides of the same coin. In the paper two alternative accounts of the relationship are proposed. According to the first one, solidarity can be defined in terms of justice, i.e. is a special variety of liberal justice, viz. social liberal justice, which, apart from the value of liberty, also stresses the importance of the value of equality. An example of such a theory is Rawls’s theory of justice, within which the value of equality is ‘encoded’ in the principle of fair equality of opportunity and in the difference principle. According to the second account, solidarity is an expression of a special type of social relationships – the so-called ‘thick relationships’, which (as opposed to ‘thin relationships’) are non-superficial, positive, their paradigmatic examples being family and friendship; in other words, the rules of solidarity are rules that are built into ‘thick relationships’. On the first account, justice and solidarity are not different, while on the second account they are different but mutually exclusive rather than mutually complementary. In the last part of the paper some remarks on the social causes of solidarity are made.